Analysis of dynamic pulmonary functions in air conditioned work environment - T. E., Anu; Bahuleyan, Biju (International Journal of Research in Medical Sciences, 2017)
Background: Thermal comfort is the condition of mind that expresses satisfaction with the thermal environment. Maintaining thermal comfort is the prime aim of heating, ventilation and air conditioning (HVAC) design engineers. Thus air conditioning has become a necessary luxury. Work environment is made comfortable to increase productivity by using air conditioners (ACs), but literature shows that long term exposure to ACs has deleterious effects. Methods: After obtaining institutional ethical clearance, the participants for this descriptive study are recruited from the staff of the hospital, based on inclusion and exclusion criteria. 40 subjects in the age group of 25-45 years using ACs for at least last 6 months for a minimum duration of 6 hours per day are included in the study. The pulmonary functions of the subjects are assessed using computerized spirometer (micro Quark) in the afternoon hours. The dynamic lung volumes obtained are compared to the predicted values according to age and sex of the individual. Results: The dynamic pulmonary function parameters such as FEV1, FVC, FEV1/FVC and PEFR were assessed. FEV1, FVC and PEFR were found to be decreased in subjects when compared to their predicted values. Marked deterioration in dynamic pulmonary functions was noted in 40-50 years age group. As the duration of exposure increases, the dynamic pulmonary functions have decreased to a statistically significant level. Pulmonary parameters are markedly decreased in subjects with BMI>23.5. Conclusions: The results of the study indicate that the subjects working in AC environment for a long duration are prone to develop restrictive lung diseases. Hence, study concludes that periodic pulmonary function assessment should be made mandatory. Further, regular maintenance of ACs is also recommended.